An amorphous superionic conductor Li3PS4‐xLiBr with high conductivity and good air stability by halogen incorporation. Issue 12 (21st August 2022) - Wang, Guoda; Dong, Pingping; Liang, Bo; Lin, Changgui; Shen, Xiang; Dai, Shixun; Jiao, Qing
Abstract: An amorphous superionic conductor is a promising solid electrolyte (SE) with excellent ionic conductivity and high energy density, which would be promising candidates for all‐solid‐state lithium‐ion batteries. However, these advantageous features alone are difficult to achieve large‐scale practical applications. Having a simple, effective synthetic route and good air stability is also critically important for SEs. Here, Li3 PS4 – x LiBr glass SE with high conductivity was obtained by simple mechanical milling and subsequent short‐term low‐temperature treatment. The site disorder between S 2− and Br − anions facilitates ionic transport. Our comparison of air stability before and after doping with halogen revealed that Br − doping well reduced the production of H2 S gas and improved the air stability of the SE.